Community-based adaptation to climate change in villages of Western Province, Solomon Islands. (July 2020) - Basel, Britt; Goby, Gillian; Johnson, Johanna
Abstract: People, local cultures and the environments they live in are complex and dynamic social-ecological systems that have evolved together over time and are continually affected by a myriad of factors, including climate and global changes. Escalating climate and global changes present an imminent threat to Pacific communities, particularly for food security, livelihoods, health and safety, cultural identity and biodiversity conservation. A participatory community-based climate change adaptation planning process was used to engage with communities on Rendova Island in Western Province, Solomon Islands to identify local adaptation priorities. The methodology recognized that local community members are the managers of the resources they use daily, have direct knowledge of the status of key local resources and have direct influence over ongoing resource governance. The study focused on two objectives: (1) identifying community priorities and documenting them in adaptation plans intended for local implementation, and (2) evaluating whether community adaptation priorities addressed key vulnerabilities identified independently using a semi-quantitative vulnerability assessment. The adaptation priorities identified by the communities encompassed: governance, leadership and planning; farming and livestock; sustainable livelihoods; natural resource management; and youth capacity building. The community adaptation priorities were found to address the key climate change vulnerabilities identified in the semi-quantitative assessment and also addressed additional drivers of social vulnerability and adaptive capacity. This finding reiterates the importance of fully inclusive and participatory vulnerability assessments and community-identification of adaptation priorities coupled with scientific climate projections to comprehensively assess the complexity of social-ecological systems. The climate change adaptation priorities have informed ongoing local actions and are intended to be used by communities, government and NGOs to focus local effort, funding and project development. A review of the suitability of the adaptation priorities by similar villages on neighbouring islands would determine the utility of scaling-up and applying these adaptations to other rural communities in the Solomon Islands, and possibly more widely in other Pacific communities. Highlights: Combined participative and semi-quantitative methodologies Community-driven vulnerability assessment and ownership of adaption actions Priorities address climate and non-climate drivers of change and degradation Adaptation actions address social factors not included in quantitative assessment Priority to educate youth with local ecological, production and traditional knowledge